Laparoscopic Appendectomy - All Raza Brohi, Naseem Mengal, Gulshan Ali Memon (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2012)
Objectives: To evaluate our early experience with laparoscopic appendectomy in children, in terms of its safety, effectiveness, technical difficulties. Methods: We reviewed the records of 60 cases involving laparoscopic appendectomy performed at Peoples University of medical & health science Nawabshah from January 2010 to December 2011. Patient age ranged from 5 to 12 years (mean, years). Forty-five patients had acute catarrhal appendicitis, seven with perforated appendicitis, five with normal appendix and three with appendicular abscess. Results; Laparoscopic appendectomy done without any difficulty in 56 patients while 4 patients was converted to open appendectomies because of technical difficulties & dense adhesions. No major postoperative complications encountered except minimal bleeding in five patients, prolong ileus seen in four patients, & pelvic abscess in 2 patients. Conclusions: Laparoscopic appendectomy is a safe and effective procedure. It takes longer operative time than open appendectomy. Length of hospitalization and incidence of postoperative complications are equivalent to those of open appendectomy. Economic benefits are difficult to assess at present. In sum, we believe that with better training, surgical techniques and equipment, laparoscopic appendectomy will eventually become the surgical procedure of choice in appendicitis.